Management of foot rot and bakanae of rice through non-chemical methods - and ANIL KUMAR, PANKAJ KUMAR, S. SUNDER, RAM SINGH* (Indian Phytopathology, 2016)
Foot rot and bakanae caused by Fusarium moniliforme Sheldon [teleomorph: Gibberella fujikuroi (Sawada) Wollenweber] is a major disease in Basmati growing states of the country including Haryana. The disease is reported to reduce the grain yield by 3.0-95.4 per cent depending on the disease incidence. Among 105 scented rice genotypes evaluated under artificial inoculation conditions during kharif 2014 and 2015 at CCSHAU Rice Research Station, Kaul, 19 genotypes viz. CN 1722-4, Haryana Basmati 1, Haryana Mahak, HKR 08-425, HKR 12-406, KMR 1-41, MAUB 2014-1, MAUB 2014-2, NDR 6222, NDR 6345, NP 973-2, Pusa 1460 (Improved Pusa Basmati 1), Pusa 1557-06-28-188-1-17, RDN 02-01-8-18-11-9, RSK-1045, Shaan, SJR 70-3-2, SJR 129 and Super Basmati were highly resistant to moderately resistant under both green house and field conditions. The regression analysis on disease score in green house and in field on each of the 105 rice genotypes showed a significant but moderate correlation (r= 0.503). Age of seedling at the time of transplanting influenced the disease incidence. A corresponding increase in grain yield was observed with decrease in disease incidence in both the scented cultivars. Among organic amendments, neem cake and press mud significantly reduced bakanae incidence while groundnut cake enhanced the disease.